2008
DOI: 10.1177/104063870802000321
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Chronic Pneumonia and Polyarthritis Syndrome Caused by Mycoplasma Bovis in Feedlot Bison (Bison Bison)

Abstract: Abstract. Mycoplasma bovis was identified by a specific lesion, conventional bacterial culture, immunohistochemistry, and polymerase chain reaction in 2 feedlot bison found dead with severe, chronic, caseonecrotic pneumonia; polyarthritis; and laryngitis. On microscopic examination, pulmonary lesions were characterized by prominent, well-defined areas of caseous necrosis and bronchiectasis. Immunohistochemical analysis of lung exhibited staining in bronchiolar epithelium and in random areas of caseous necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Although there are publications describing the importance of such diseases as malignant catarrhal fever, 8 anthrax, 11 and brucellosis 9 in bison, there is only a single publication reporting mycoplasmosis in bison. 2 The current report investigates an outbreak of disease in bison characterized by high morbidity and mortality, in which M. bovis was identified as the cause.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are publications describing the importance of such diseases as malignant catarrhal fever, 8 anthrax, 11 and brucellosis 9 in bison, there is only a single publication reporting mycoplasmosis in bison. 2 The current report investigates an outbreak of disease in bison characterized by high morbidity and mortality, in which M. bovis was identified as the cause.…”
mentioning
confidence: 99%
“…7 Although there are several reports on Mycoplasma-induced diseases in bovines, 3,10 only 1 report was found on Mycoplasma infection in bison. 2 Mycoplasma bovis infection causes significant economic loss to the cattle industry. 6,7 Once on the verge of extinction, bison numbers have substantially increased from approximately 1,000 in the late 1800s to approximately 500,000 in North America.…”
mentioning
confidence: 99%
“…Although the usefulness of the Bio-X M. bovis ELISA in bison testing was demonstrated earlier (Register et al 2013a) the possibility of false positive results in this study cannot be excluded. Nevertheless it has been previously demonstrated that M. bovis does infect bison and can cause serious disease problems (Dyer et al 2008, Janardhan et al 2010, Register et al 2013b. Further studies are required to show the true mycoplasma status of bison and to determine the cause of the lesions observed.…”
Section: Resultsmentioning
confidence: 99%
“…In Poland serological evidence in one bison (Krzysiak et al 2014); pneumonia, larynCorrespondence to: K. Dudek, e-mail: katarzyna.dudek@piwet.pulawy.pl, tel. : +48 0-81 889 30 21 gitis, arthritis, synovitis and tenosynovitis in feedlot bison (Dyer et al 2008); arthritis, pleuritis and abscesses in the lung with mortality above 27% (Janardhan et al 2010); fatal reproductive disorders and abortion in American bison in which bronchopneumonia, pleuritis and coagulation necrosis in the lung were also observed (Register et al 2013b . Specific antibodies to these mycoplasmas in bison have not been observed (Krzysiak et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Tulathromycin, with a molecular formula of C 41 H 79 N 3 O 12 and molecular mass of 806.23 ( Figure 1), is a semi-synthetic macrolide antibiotic approved to treat bovine and swine bacterial respiratory disease but not for white-tailed deer or bison. [5][6][7][8][9] It is also used as a preventative measure in cattle feedlots to reduce the risk of contracting respiratory disease, such as those pathogens associated with Pasteurella, Mannheimia, Actinobacillusm, and Mycoplasma species.…”
Section: Introductionmentioning
confidence: 99%